Impact of Community-based Rangeland Management (CBRM) and Livestock Marketing Interventions on Adaptive Capacity, Food and Nutrition Security, and Greenhouse Gas Emissions in Extensive Livestock Systems in Kenya - Odhong, Charles; Van Djik, Suzanne; Wahome, Raphael; Chepkorir, Vicky; Kihara, Francis; Kamadi, Victor; Radeny, Maren A.O. (International Livestock Research Institute, 2025)
In Kenya, the Arid and Semi-Arid Lands (ASALs) support over 70% of the country's livestock and 85% of its wildlife. Pastoralists, who practice extensive livestock production, dominate these regions, contributing about 46.3% of the nation's beef production. Livestock production systems in Kenya’s rangelands face several challenges that affect livestock productivity and increase mortality. This low-input system relies on natural or semi-natural vegetation in rangelands, where pastoralists—whether transhumant or nomadic—derive over half their income from livestock and livestock products. The challenges experienced can broadly be categorized into: i) Environmental (climate change, soil erosion, declining biodiversity, lack of water, increased spread of livestock diseases); ii) Social (conflict, increased demand for land); and iii) Governance (changes in land tenure systems, elite influence on decision making, weakening traditional institutions). At the same time, livestock systems also contribute to climate change primarily through the production of greenhouse gases (nitrous oxide and methane) mainly from enteric fermentation, fodder, and manure management. Interventions to improve productivity in pastoral livestock systems in Kenya have mainly focused on improving livestock production, strengthening marketing systems and rangeland restoration. To increase production, interventions have focused on provision of animal health services e.g. disease control programs. To strengthen markets, interventions have focused on reducing marginalization of pastoralist and enhancing access to local and external markets. To restore rangelands, management interventions have focused on addressing the cause of degradation. Rangeland restoration interventions implemented by communities and various stakeholders include: i) rotational of grazing on pastures; ii) reseeding of rangelands; iii) reduction of livestock numbers; iv) variation of the species of livestock kept by the communities; and v) modification of grazing times for individuals and communities. Interventions to improve productivity and restore rangeland landscapes have resulted in better animal nutrition with positive impact on health and fertility - healthier animals, which emit less GHG to produce more output (e.g. early attainment of market weight).